Science of the Cosmos, Science of the Soul : the pertinence of Islamic cosmology in the modern world - Chittick, William C. (Oxford : Oneworld, 2007)
Islamic Intellectualism is dead: or so argues William Chittick in this new book. Whilst many may say that Islamic studies thrives as a subject, Chittick points to the words of one of his former Professors when describing young colleagues: they know everything one can possibly know about a text, except what it says. Indeed, Chittick states that it is impossible to understand ancient Islamic texts without the years of contemplative study that are anathema to the modern education system. While modern intellectuals with faith often treat their studies and faith in two separate spheres, Chittick argues that it is essential to return to the ways of the ancient Sufis, who viewed knowledge of the soul, the world, and God as an extension of the same thing.
A vanishing heritage -- Intellectual knowledge -- The rehabilitation of thought -- Beyond ideology -- The unseen men -- The anthropocosmic vision -- The search for meaning.
Includes bibliographical references and index.
Keywords: Islamic cosmology; Sufism; Islam; Islam and science